2012
DOI: 10.1111/bdi.12005
|View full text |Cite
|
Sign up to set email alerts
|

State‐related alterations of gene expression in bipolar disorder: a systematic review

Abstract: There is evidence of some genes exhibiting state-related alterations in expression in bipolar disorder; however, this finding is limited by the lack of replication across studies. Further prospective studies are warranted, measuring gene expression in various affective phases, allowing for assessment of intraindividual differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 81 publications
1
30
0
1
Order By: Relevance
“…In fact, only few studies on potential biomarkers in mood disorders have included longitudinal assessment of healthy control individuals [52,53]. We have previously suggested a number of methodological considerations, including repeated measures and within-subject comparisons, for studies of other potential biomarkers in BD [54,55] and have applied these in clinical studies [56,57]; these methodological issues have recently been emphasized by others [58]. Future clinical case-control studies of GSK-3β should consider including repeated measures of both cases and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only few studies on potential biomarkers in mood disorders have included longitudinal assessment of healthy control individuals [52,53]. We have previously suggested a number of methodological considerations, including repeated measures and within-subject comparisons, for studies of other potential biomarkers in BD [54,55] and have applied these in clinical studies [56,57]; these methodological issues have recently been emphasized by others [58]. Future clinical case-control studies of GSK-3β should consider including repeated measures of both cases and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene and genome-wide microarray expression analyses of postmortem human brains have shown that transcriptional dysregulation plays a role in the etiology of bipolar disorder (for a review, see reference 3). Some notable genes have been identified through these studies (4,5); however, very few passed corrections for multiple testing, and findings from these studies have largely not been replicated (3,5,6). RNA sequencing, a technique that takes advantage of the recent development of high-throughput sequencing technologies, offers a number of advantages in comparison to previous methodologies, such as microarray studies, in that it provides direct estimates of transcript abundance, as well as nucleotide-level sequence.…”
Section: Methodmentioning
confidence: 99%
“…Instead, currently available data reinforce the polygenic basis of BD, with significant state-related abnormalities in gene expression. Nevertheless, some findings regarding genes that display state-related changes in expression in BD were not replicated across studies (Munkholm et al 2012). …”
Section: Methodsmentioning
confidence: 99%